A sustainable application for the extraction of lichen metabolites from Usnea cornuta: nontargeted metabolomics and antioxidant activity (2023)
In this study, isolation and purification of lichen substances from Usnea cornuta were performed using conventional solvents, green solvents and green technologies. In addition, several lichen compounds were tentatively identified by UHPLC/ESI/MS/MS and usnic acid, diffractaic and galbinic acids were quantified as well. Limonene, ethyl lactate and methanol, were compared regarding their extraction properties and antioxidant capacities, determined by DPPH, ORAC, and FRAP assays. In the ethyl lactate, methanol and limonene extracts, 28 compounds in all, were detected for the first time by high resolution UHPLC-MS/MS fingerprinting. Untargeted metabolomics tentatively identified 14 compounds from the methanolic extract, 4 from limonene extract, and 20 metabolites from ethyl lactate extract. The green extract of ethyl lactate showed a similar antioxidant capacity to toxic methanol extract, except at ORAC assay where it was higher. Therefore, ethyl lactate can replace methanol, to provide more sustainable green chemistry methods.